2014
DOI: 10.1177/1076029613520465
|View full text |Cite
|
Sign up to set email alerts
|

Thrombophilic Mutations and Polymorphisms, Alone or in Combination, and Recurrent Spontaneous Abortion

Abstract: Generally, recurrent spontaneous abortions (RSAs) have no identifiable cause; yet, vascular alterations during pregnancy may be associated with pregnancy loss. Therefore, we evaluated the association between thrombophilic mutations and RSAs. This case-control study was conducted in 112 patients who had RSAs and 98 health control women. Genomic DNA was extracted from whole blood, and polymorphism genotyping was conducted using polymerase chain reaction. The following 6 genetic variants were analyzed: factor V L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 54 publications
(97 reference statements)
0
28
0
Order By: Relevance
“…In addition, PAI-1 4G/5G polymorphism was associated with increased PAI-1 concentrations and hypofibrinolysis and contributed to early pregnancy loss [ 7 ]. Many studies assessed the association between PAI-1 4G/5G polymorphism and RPL risk [ 8 29 ]. However, the result was still uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PAI-1 4G/5G polymorphism was associated with increased PAI-1 concentrations and hypofibrinolysis and contributed to early pregnancy loss [ 7 ]. Many studies assessed the association between PAI-1 4G/5G polymorphism and RPL risk [ 8 29 ]. However, the result was still uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Because of no association between the presence of polymorphisms with recurrent pregnancy loss and maternal thrombotic events, in this study, screening of existence of APC resistance was recommended in women with recurrent miscarriages. Recently, Lino et al (2015) [17] showed no association between studied polymorphisms (FVL, PTM, MTHFR, C677T, MTHFR A1298C, and FXIII V34L) and the occurrence of recurrent abortion, but these results have a substantial value to carry out a meta-analysis. However none of these researches has tried to correlate with cytogenetic results of abortions samples.…”
Section: Discussionmentioning
confidence: 98%
“…These authors demonstrated the fundamental importance of cytogenetic studies of chromosomal abnormalities in miscarriages samples, prior to investigating other possible causes in couple with a history of RSA. Some studies showed the cytogenetic abnormalities and hereditary thrombophilias in RSAs, the association with risk factors, between the presence of FVL, FII G20210A mutations and patients with normal karyotype [17][18][19]. In 1999, Meinardi et al [20] examined the FVL in mothers with spontaneous abortions and suggested the study of hereditary thrombophilia in fetus and of the clinical implications related with embryo genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Many underlying mechanisms have been recognized for RPL, including chromosomal defects ( Rajcan-Separovic et al, 2010 ), endocrinopathies ( Ke, 2014 ) (thyroid diseases and diabetes), uterine malformations ( Jaslow, 2014 ), and autoimmune diseases ( Kwak-Kim et al, 2013 ). In addition, thrombophilic mutations ( Lino et al, 2014 ) have been suggested as leading to alterations in embryonic formation, migration, implantation and placentation; in the past three decades, this area has become a field of extensive study with the goal of increasing the rate of live births in these patients.…”
Section: Clinical Application Of the Use Of Heparins During The Firstmentioning
confidence: 99%